2021
DOI: 10.3390/pathogens10060748
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Two Western Mediterranean West Nile Virus Lineage 1 Isolates in Experimentally Infected Red-Legged Partridges (Alectoris rufa)

Abstract: West Nile virus (WNV) is the most widespread flavivirus in the world with a wide vertebrate host range. Its geographic expansion and activity continue to increase with important human and equine outbreaks and local bird mortality. In a previous experiment, we demonstrated the susceptibility of 7-week-old red-legged partridges (Alectoris rufa) to Mediterranean WNV isolates Morocco/2003 and Spain/2007, which varied in virulence for this gallinaceous species. Here we study the pathogenesis of the infection with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The feather pulps were frequently infected in 9/15 geese up to 14 dpi, as detected by RT-qPCR, containing up to 10 6.1 TCID 50 /mL (G 8, 3 dpi), as proven by virus titration (Table S6). Thus, the virus was detectable in the feather pulps for a longer duration than in the blood in both our study and in red-legged partridges (Alectoris rufa) infected with a WNV lineage 1 strain [42]. Therefore, our results not only support direct horizontal transmission cycles via pulp by feather pecking but also indicate an alternative method for collecting and analyzing feather pulps for the monitoring of WNV in live/succumbed (wild/zoo) birds.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The feather pulps were frequently infected in 9/15 geese up to 14 dpi, as detected by RT-qPCR, containing up to 10 6.1 TCID 50 /mL (G 8, 3 dpi), as proven by virus titration (Table S6). Thus, the virus was detectable in the feather pulps for a longer duration than in the blood in both our study and in red-legged partridges (Alectoris rufa) infected with a WNV lineage 1 strain [42]. Therefore, our results not only support direct horizontal transmission cycles via pulp by feather pecking but also indicate an alternative method for collecting and analyzing feather pulps for the monitoring of WNV in live/succumbed (wild/zoo) birds.…”
Section: Discussionsupporting
confidence: 66%
“…This is in accordance with the viral load seen in RT-qPCR (Figure 6, Table S5), showing positive IHC staining only with CT values below 20. Furthermore, in other studies, IHC was positive only at high viral loads detected by RT-qPCR and at early time points pi because of the lower sensitivity compared to RT-qPCR [42,58,59]. This lower sensitivity could be due to the fact that the antibody of the IHC detects a different target than the RT-qPCR or that only many small amounts of antigen are present in the tissue.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, it was found to reach viremic levels high enough to infect mosquitoes (i.e., it is a competent host). Furthermore, it is useful to discriminate between WNV strains in terms of pathogenicity ( Sotelo et al., 2011 ; Pérez-Ramírez et al., 2018 ; Gamino et al., 2021 ). However, the susceptibility of this wild bird species to USUV infection and disease, as well as its competence for virus transmission and overall epidemiological role, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to WNV pathogenesis Gamino et al [ 7 ] delved into the pathogenesis of WNV in birds. In a previous study the authors demonstrated the susceptibility of red-legged partridge ( Alectoris rufa ) to two Mediterranean WNV strains from Morocco and Spain via experimental infection, showing higher mortality and morbidity in the birds infected with the Moroccan isolate.…”
mentioning
confidence: 99%